(untitled) (Revista Ciência Agronômica, 2018)
This study verified the effect of valine on the zootechnical performance, percentage composition and growth of skeletal muscle fibre in fingerlings of Nile tilapia. A total of 270 fish (average initial weight 1.57 ± 0.05 g and total initial length 4.16 ± 0.46 cm) were used, distributed in 18 tanks (250 litres), in a completely randomised design with six treatments and three replications. Six diets (26.81% DP and 3200.00 kcal DE) were formulated with increasing levels of valine (0.82, 0.86, 0.98, 1.04, 1.10 and 1.26% of the diet). The zootechnical performance, percentage composition of the fish, and muscle-fibre distribution were evaluated. There was no effect from the different levels of valine (P>0.05) on zootechnical performance, percentage composition or the frequency distribution of muscle fibre. The addition of 0.82% valine (2.65% crude protein valine) is recommended in the diet of Nile tilapia fingerlings.